1979
DOI: 10.1121/1.382335
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of sound in highly concentrated suspensions and emulsions

Abstract: The absorption of sound in emulsions and suspensions is due to viscous and thermal transport processes occurring at the interface of the nonhomogeneities, as well as to the intrinsic absorption in the materials comprising the system. For highly concentrated mixtures, multiple scattering is shown to play an important role. Following the arguments of Waterman and Truell [J. Math. Phys. 2, 512 (1961)], the behavior of the scattering medium may be specified explicitly in terms of the number of scatterers per unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Nevertheless, note that multiple-particle effects have also been observed in this kind of system [44]. On the other hand, Davis [45,46] and Sayers [47] analysed dispersions of much larger particle sizes than those considered here. As indicated by Kytömaa [5], this favours the lossless redirection of acoustic waves as described by the above mentioned multiple scattering theories, which in this case becomes the dominating mechanism of sound attenuation.…”
Section: Incorrect Modelling Of the Frequency Dependencementioning
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, note that multiple-particle effects have also been observed in this kind of system [44]. On the other hand, Davis [45,46] and Sayers [47] analysed dispersions of much larger particle sizes than those considered here. As indicated by Kytömaa [5], this favours the lossless redirection of acoustic waves as described by the above mentioned multiple scattering theories, which in this case becomes the dominating mechanism of sound attenuation.…”
Section: Incorrect Modelling Of the Frequency Dependencementioning
confidence: 61%
“…However, the models of both Waterman and Truell and Lloyd and Berry have been used successfully in other contexts to interpret acoustic attenuation [14,15,31,[45][46][47]. These results may be understood by looking at the dominating attenuation mechanisms.…”
Section: Incorrect Modelling Of the Frequency Dependencementioning
confidence: 99%
“…This leads to an attenuation coefficient which is linear in solid concentration, but examination of attenuation data for suspensions shows that this linearity is at best true only for very dilute concentrations of particles. In contrast, Davis (1979) showed that a theory including multiple scattering resulted in an attenuation coefficient with a second order correction term.…”
Section: Introductionmentioning
confidence: 99%
“…These empirical functions also enable some conclusions on underlying molecular mechanisms. , We nevertheless additionally applied relaxation functions which are based on physical models of the liquid structure and microdynamics of the mixtures. Among the functions considered has been a sum of k Debye terms ( k = 1, 2, ...) representing chemical relaxations, expressions that reflect dissipation of sound energy at internal interfaces of microheterogeneous samples, and particularly relations that result from the assumption of concentration fluctuations in binary mixtures including a jump- diffusion model. , We found the smallest values in the variance χ 2 , combined with a self-consistent dependence of the parameter values ξ 1 , ..., ξ P on the mixture composition, if the model spectral function was used. The second term on the right-hand side of this equation represents the Romanov-Solov'ev relaxation of sound attenuation by noncritical, noncorrelated fluctuations in the mixture concentration. ,, Again, A RS denotes an amplitude, is a diffusion time, and I is a scaling function which can be written in an explicite form: …”
Section: Results and Analytical Description Of Measured Spectramentioning
confidence: 88%